Diabetes Support Groups Improve Patient’s Compliance and Control Blood Glucose Levels - Zamrotul Izzah; Budi Suprapti; Toetik Aryani; Aniek S. Budiatin; Mahardian Rahmadi; Pharmasinta P. Hapsari; Fathia Ramadiani; Dewi W. Shinta; Mareta R. Andarsari (Universitas Padjadjaran, 2013)
Providing information is not enough to improve diabetic patient’s compliance and achieve goals of therapy. Patient’s good awareness as well as emotional and social supports from family and community may play an important role to improve their compliance and clinical outcomes. Therefore, diabetes support groups were developed and each support group consisted of two pharmacists, two nurses, diabeticpatients and their family members. A total of 70 type 2 diabetic patient’s were enrolled and randomized into support group 1 and support group 2. Patients in the group 1 received information leaflets only, while patients in the group 2 received pharmacist counselling and information leaflets at each meeting. Patient’s awareness of diabetes and compliance with medications were assessed by a short questionnaire at baseline and final follow-up. Blood glucose and cholesterol levels were also evaluated in both groups.At the end of study, the overall patient’s awareness and compliance improved by 61.5%. The random and fasting blood glucose levels decreased over than 30% in the group 2 and around 14% in the group 1. This study reveals that collaboration between health care professionals and community in the diabetes support group might help diabetic patients to increase their knowledge and compliance with the diabetes therapy as well as glycaemic control.Key words: Diabetes, group awareness program, pharmacist, patient counselling Kelompok Dukungan terhadap Diabetes Meningkatkan Kepatuhan dan Kontrol Kadar Glukosa Darah PasienMenyediakan informasi tidak cukup untuk meningkatkan kepatuhan pasien diabetes dan mencapai tujuan terapi. Kesadaran pasien serta dukungan emosional dan sosial dari keluarga dan masyarakat dapat memainkan peran penting untuk meningkatkan kepatuhan dan hasil klinis. Oleh karena itu, kelompok pendukung diabetes dikembangkan dan masing-masing kelompok pendukung terdiri atas dua apoteker, dua perawat, pasien diabetes dan anggota keluarga mereka. Sebanyak 70 pasien diabetes tipe 2 yang terdaftar dan acak ke dalam kelompok dukungan 1 dan kelompok dukungan 2. Pasien dalam kelompok 1 menerima selebaran informasi saja, sedangkan pasien di kelompok 2 menerima konseling dari apoteker dan informasi diabetes pada setiap pertemuan. Kesadaran Pasien diabetes dan kepatuhan dengan obat dinilai oleh kuesioner singkat pada awal dan akhir. Kadar glukosa darah dan koleste-rol juga dievaluasipada kedua kelompok. Pada akhir penelitian, kesadaran dan kepatuhan pasien secara keseluruhan meningkat 61,5%. Kadar glukosa darah acak dan puasa menunjukkan penurunan 30% pada kelompok 2 dansekitar 14 % pada kelompok 1. Penelitian ini mengungkapkan bahwa kolaborasi antara profesional perawatan kesehatan dan masyarakat dalam kelompok pendukung diabetes dapat membantu pasien diabetesuntuk meningkatkan pengetahuan dan kepatuhan mereka dengan terapi diabetes serta kontrol glikemik. Kata kunci: Diabetes, program penyadaran kelompok, apoteker, konseling pasien